Clinicopathologica Epidemiological Characteristics and Change Tendencies of Renal Cell Carcinoma in Shanxi Province of China from 2005 to 2014 - Bai, Tao (PLoS One, 2015)
OBJECTIVES: RCC is the most common solid renal malignancy in adults worldwide. To provide the insight of clinicopathologica epidemiological characteristics and change tendencies of renal cell carcinoma (RCC), 2154 cases were collected from Shanxi Province of China, including diagnose time, age, gender, tumor size, Fuhrman grade, tumor stage, tumor location, local advance or distant metastasis and first symptom from 2005 to 2014. This retrospectively investigation, as its general objective, was to analyze the clinicopathologica epidemiological characteristics and the change tendencies of RCC. METHODS: Between 2005 and 2014, 2154 patients who were diagnosed with RCC in three large tertiary hospitals at Shanxi Province were included. The patients’ demographic features, pathological diagnoses and metastatic statuses were analyzed. Statistics methods include the chi-squared test, analysis of variance, Spearman’s correlation analysis, Logistic regression and ARIMA modeling. RESULTS: Of the 2154 included patients, the constituent ratio of female /male was 63.1% and 36.9%, with the median age of 57 years old. Fuhrman grade distributions differed significantly between males and females (p = 0.024). Also, a significant difference in tumor size was found by different clinical stages (p < 0.001), with a linear correlation (p < 0.001). Moreover, Spearman’s analysis indicated tumor grade has a negative correlation with female (p = 0.009) and a positive correlation with tumor size (p = 0.000). It was found that the tumor diameter is bigger in the left side (p = 0.022). Furthermore, the metastasis rate was higher in the bigger tumor (p < 0.001) and the left-sided tumors (p = 0.027). Logistic regression also showed that tumor size is a risk factor for metastasis (OR = 1.724). The risk of local advance or distant metastasis in the left kidney was 1.6-fold greater than that of the right kidney. From 2005 to 2014 the number of RCC cases gradually increased (mainly for pathological grade II and III, but grade I and IV), while the average tumor size decreased, showing the severity increase mildly. Base on the results of a time series analysis-prediction the average RCC size would continue to decrease from the first quarter of 2015 to the fourth quarter of 2016. CONCLUSIONS: The cases of RCC increased from 2005 to 2014 with clear cell type as the main pathological type in this population. The characteristics in the constituent ratios of the RCC vary depending on gender, pathological grade, tumor size, and location, which may be the important factors impacting treatment and prognosis.